2013
DOI: 10.17221/702/2012-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various organic materials on soil aggregate stability and soil microbiological properties on the Loess Plateau of China

Abstract: A field experiment was conducted to examine the influence of various organic materials on soil aggregate stability and soil microbiological properties on the Loess Plateau of China. The study involved seven treatments: no fertilizer (CK); inorganic N, P, K fertilizer (NPK); low amount of maize stalks plus NPK (LSNPK); medium amount of maize stalks plus NPK (MSNPK); high amount of maize stalks plus NPK (HSNPK); maize stalk compost plus NPK (CNPK); cattle manure plus NPK (MNPK). The organic fertilizer treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 18 publications
9
23
0
Order By: Relevance
“…This corresponds with Wang et al (2013), who found that the organic fertilizer treatments improved soil aggregate stability and soil microbiological properties compared with unfertilized and mineral NPK treatments.…”
supporting
confidence: 86%
“…This corresponds with Wang et al (2013), who found that the organic fertilizer treatments improved soil aggregate stability and soil microbiological properties compared with unfertilized and mineral NPK treatments.…”
supporting
confidence: 86%
“…These results indicate a negative effect of mineral N application on the stability of soil aggregates and the possibility of elimination of this negative effect using the application of compost or organic-mineral substances. The results are consistent with the work of Wang et al (2013); Zhang et al (2016b); Bronick and Lal (2005). Soinne et al (2016) warn that the destruction of soil structure exhibiting a reduced stability of aggregates leads to a significant reduction of soil functions, such as changing soil moisture conditions and deterioration of soil infiltration capacity.…”
supporting
confidence: 89%
“…The microcosm method was validated to provide a good access for studying the effect of litter type on soil properties during the early stage of decomposition (Taylor and Parkinson 1988, Vargas et al 2006, Wang et al 2010. Since soil microbial biomass, enzyme activities, and DOC were suggested as early indicators of biological changes, and even important indicators of soil quality (Liang et al 1998, Hu et al 2006, Wang et al 2013, this study should provide some valuable information for the soil fertility management of the local pine plantations.…”
mentioning
confidence: 99%